Association of Low Back Pain and Mood Disorders with Primary Dysmenorrhea in University-Going Young Females - Abdul Malik; Orakzai, Sheeba; Shah, Syeda Saniya; Khalid, Wishal; Aziz, Oqab; Ilyas, Muskan (Indus Journal of Bioscience Research, 2025)
Background: Primary dysmenorrhea (PD), or painful periods, is a common problem in young women. It often comes with both physical discomforts, like low back pain, and emotional issues such as anxiety or depression. However, not much research has been done on how these problems are connected, especially among university students in Pakistan. Objective: To find out whether there is a link between low back pain and mood disorders with primary dysmenorrhea in university going young female students. Methods: In this cross-sectional study, 377 female university students in Peshawar, ages 18 to 30, was participated. Standard questionnaires were used to assess menstrual pain (WaLIDD), back pain (Oswestry Disability Index), and mood disorders (Mood Disorder Questionnaire). Data were analyzed by using SPSS, and chi-square tests were used to find out the association of low back pain and mood disorders with primary dysmenorrhea. Results: Most participants (69.8%) had moderate to severe menstrual pain. Mood disorders were found in 64.7% of students, and 63.4% reported moderate to severe low back pain. There was a strong significant link between menstrual pain, low back pain and mood disorders (p = 0.000). Chi-square analysis revealed that there no significant association between age and low back (p = 0.713). Conclusion: There is a clear connection between primary dysmenorrhea, low back pain, and mood disorders in university-going young females. These results show the need for better support and treatment—both physical and emotional—especially using physiotherapy and awareness programs to improve student’s health and daily life.